ACTIVITIES OF THE AIR TRANSPORT SYSTEM OF THE REPUBLIC OF UZBEKISTAN IN PANDEMY : TENDENCIES AND EXPERIENCES - Nasridinov Javoxir Djamaledinovich, (EPRA International Journal of Research and Development (IJRD), 2022)
The article analyses the level of negative impact of Covid19 outbreak on the air transportation of Uzbekistan on development of national economy and reviews all activities which have been carried out by government for improvement of the aviation sphere. Recommendations and proposals on further development of the aviation industry are developed as well.